UNDERSTANDING THE ROLE OF PLASTIC RECYCLERS IN PLASTIC WASTE’S CIRCULAR SUPPLY CHAIN GOVERNANCE IN INDONESIA - Putra, Andi Manggala; Adhariani, Desi; Dewi, Miranti Kartika (I-iECONS e-proceedings, 2023)
This study aims to examine the role of plastic recyclers in managing the plastic waste’s circular supply chain governance in Indonesia. The data was gathered through interviews and on-site visits to plastic waste stakeholders five plastic recycling plants in Indonesia. The findings reveal that the plastic waste’s circular supply chain governance shows a combination of approaches, particularly in the relationship between recyclers and junk shops based on seven aspects of relational-contractual analysis. The governance structure of the plastic waste’s circular economy supply chain tends to be relational, considering historical relationships, environmental uncertainties, power imbalances, and fairness perceptions. On the other hand, recycling factories strictly adhere to a contractual governance pattern concerning risk perception. This research provides valuable insights into circular economy governance in a developing economy and offers policy implications for the governance of the plastic circular economy supply chain in Indonesia.